2018
DOI: 10.3389/fcimb.2018.00428
|View full text |Cite
|
Sign up to set email alerts
|

Serum Levels of Soluble CD40 Ligand and Neopterin in HIV Coinfected Asymptomatic and Symptomatic Visceral Leishmaniasis Patients

Abstract: Human Immunodeficiency Virus (HIV) co-infection drastically increases the risk of developing overt visceral leishmaniasis (VL). The asymptomatic Leishmania infection window constitutes an opportunity to identify those HIV patients at highest risk by defining early markers associated with disease susceptibility or resistance. As intracellular parasite killing is essential, we investigated whether serum markers of macrophage activation were notably affected in HIV patients with an asymptomatic Leishmania infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“… 15 In a separate study, it was shown that decreased levels of CD40L and increased levels of neopterin, a molecule associated with activation of macrophages, were present in the plasma of HIV/VL as compared to patients with HIV. 16 Van den Bergh et al. suggested that myeloid-derived suppressor cells might play a role in severely immunocompromised HIV/VL co-infected patients.…”
Section: Introductionmentioning
confidence: 99%
“… 15 In a separate study, it was shown that decreased levels of CD40L and increased levels of neopterin, a molecule associated with activation of macrophages, were present in the plasma of HIV/VL as compared to patients with HIV. 16 Van den Bergh et al. suggested that myeloid-derived suppressor cells might play a role in severely immunocompromised HIV/VL co-infected patients.…”
Section: Introductionmentioning
confidence: 99%
“…Little is known about CD40 expression on monocytes in VL patients. The levels of the soluble form of its ligand, sCD40L, have been shown to be lower in plasma of HIV/VL patients as compared to patients with HIV asymptomatically co-infected with Leishmania parasites [29]. De Oliveira et al .…”
Section: Discussionmentioning
confidence: 99%
“…10 non-endemic male controls with no prior history of VL were recruited amongst the staff of the University of Gondar. The median ages of the three cohorts were similar: VL patients at ToD: 25 [20][21][22][23][24][25][26][27][28][29][30]; VL patients at EoT: 23.5 [18.5-26.8] and controls: 24 [20.5-27.3] years old (p=0.7495). Informed written consent was obtained from each patient and control.…”
Section: Subjects and Sample Collectionmentioning
confidence: 99%
“…In further analysis, the sCD40L levels also negatively correlated with the spleen size in the SbV + NAC group, but not in the control SbV group. sCD40L has been previously demonstrated as an important biomarker of VL disease, associated with better outcomes, stimulating resolutive immune response ( Okwor and Uzonna, 2016 ; Adriaensen et al., 2018 ). Previous data of our group, using patients from the same local of this study, demonstrate that sCD40L is an important biomarker in VL, indicating a favorable evolution during and after treatment, negatively correlating with the spleen sizes and parasite load in patients with VL ( de Oliveira et al., 2013 ).…”
Section: Discussionmentioning
confidence: 99%